The incidence and risk factors of chronic rejection in acutely rejected pediatric liver transplantation - S. M. Dehghani; I. Shahramian; M. Ayatollahi; F. Parooie; M. Salarzaei; M. Bahmanyar; A. Sargazi; M. Delaramnasab (Вестник трансплантологии и искусственных органов, 2022)
Background. Chronic graft rejection (CR) represents an increasing concern in pediatric liver transplantation (LT). Risk factors of CR in this population are uncertain. In present study, we aimed to ascertain if clinical parameters could predict the occurrence of CR in LT children.Methods. We retrospectively analyzed the results from 47 children who had experienced acute hepatic rejection in Namazee hospital, Shiraz, Iran during 2007–2017.Results. Out of 47 children, 22 (46.8%) and 25 (53.2%) were boys and girls respectively. Ascites, gastrointestinal bleeding, and spontaneous bacterial peritonitis were observed in 20 (44.4%), 14 (31.1%), and 4 (9.1%) respectively. Posttransplant vascular and biliary complications were observed in 3 (7%) and 4 (9.3%) cases respectively. The mean time from LT to normalization of liver enzymes was 14.2 ± 7.5 days. The mean of acute rejection episodes was 1.4 ± 0.6 (median = 1 (22, 46.8%), range of 1–3). Six (12.7%) patients experienced CR. The mean time from LT to CR was 75 ± 28.4 days. A significant association was found between CR and patients’ condition (being inpatient or outpatient) before surgery (P = 0.03). No significant relationship was found between CR and post-transplant parameters except for biliary complications (P = 0.01). Both biliary complication (RR = 33.7, 95% CI: 2.2–511, P = 0.01) and inpatient status (RR = 10.9, 95% CI: 1.1–102.5, P = 0.03) significantly increased the risk of CR.Conclusion. Being hospitalized at the time of LT, and development of biliary complications might predict risk factors for development of CR in LT children.